(untitled) (Intent Research Scientific Journal, 2024)
This paper will be of two chapters. The first chapter will discuss the three important aspects of the novel in addition to the biography of the author. The second chapter will tackle the theme of Inhumanity in The Grapes of Wrath in addition to a Critical Reception of The Grapes of Wrath. Steinbeck painfully and again emphasizes that the refugees’ immense suffering is brought on by other people, not by ill luck or bad weather. People are divided into wealthy and poor, landowners and tenants by historical, social, and economic factors, and those in positions of power fight ferociously to hold onto their privileges. The novel distinguishes the affluent from the destitute by drawing a simple line through the population and attributes all evil and misery in the world on this split. Because of the way his writing captures the hardships of a typical dust bowl homeless family just trying to start over, The Grapes of Wrath has become and will continue to be regarded as a classic that countless people adore.